Non-linear Panel Data Liquidity Model of Islamic and Conventional Banks - Wahida Ahmad; Nur Hazimah Amran (Information Management and Business Review, 2023)
Banks and liquidity risk are synonymous with each other due to inevitable asset-liability mismatches derived from deposit and lending activities. The study aims to investigate this issue by highlighting a new insight into the non-linear function between profitability and liquidity risk. With the aspiration to include both Islamic and conventional banks from nine Asia-Pacific countries, this study involves the unbalanced panel data of a 10-year period that covers from 2011 to 2020. The final sample ends with 285 banks and 2,116 observations. The study employs a quadratic random effect model with clusters adjusted errors comprised of five interest predictors namely profitability, credit risk, bank capital, income diversification and bank size. The findings discover profitability, bank capital, income diversification, size and economic condition play vital roles in managing banks liquidity. The findings reveal the existence of moral hazard for larger and highly capitalized banks with greater exposure to liquidity risk. High-margin banks are also prone to maintain lower liquidity levels, thus exposed to greater risk. Banks are advocated to elevate higher earnings and maintain adequate levels of capital and assets with the caution of moral hazard issues. Therefore, the regulatory body in each country is proposed to intervene and monitor especially the higher margin banks to lessen the moral hazard issue.